1999
DOI: 10.1037/1076-8971.5.2.439
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hearsay testimony on conviction rates in trials of child sexual abuse: Toward balancing the rights of defendants and child witnesses.

Abstract: The authors examined how mock jurors respond to the testimony of hearsay witnesses in trials of child sexual abuse. In Experiment 1, participants watched a highly realistic videotape of a sexual abuse trial. In one condition, the child victim/witness testified on her own behalf; in the hearsay condition, the child's mother testified in lieu of her daughter. Conviction rates were significantly higher in the child condition versus the hearsay condition. In Experiment 2, participants read a trial summary of a sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…For example, Ross, Lindsay, and Marsil (1999) suggest that allowing hearsay testimony in the courtroom may lead jurors to believe that the defendant is guilty, by implying that the child must be protected from the defendant. Another problem, and one that has been the subject of study, is that hearsay testimony provides jurors with the "gist" or second-hand account of the original interview.…”
Section: Influence Of Hearsay Testimony On Jurorsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Ross, Lindsay, and Marsil (1999) suggest that allowing hearsay testimony in the courtroom may lead jurors to believe that the defendant is guilty, by implying that the child must be protected from the defendant. Another problem, and one that has been the subject of study, is that hearsay testimony provides jurors with the "gist" or second-hand account of the original interview.…”
Section: Influence Of Hearsay Testimony On Jurorsmentioning
confidence: 98%
“…Jurors may lose important information that would allow them to evaluate the child's account. Several studies (Golding, Sanchez, & Sego, 1997;Myers, Redlich, Goodman, Prizmich, & Imwinkelried, 1999;Ross et al, 1999;Warren, Nunez, Keeney, Buck, & Smith, 2002) illustrate how various hearsay accounts can influence jurors decision making depending on the amount and type (i.e., "gist" vs. verbatim) of information provided by the hearsay witness.…”
Section: Influence Of Hearsay Testimony On Jurorsmentioning
confidence: 99%
“…The reasoning behind this exception is the belief that these statements are made in a state of excitement and therefore unlikely to be premeditated falsehoods. Ross, Lindsay, and Marsil (1999) argued that even though courts allow hearsay under special circumstances, potential negative biases arise for both the defendant and the victim during jury decision-making. These negative biases, discussed originally with regard to child abuse cases, apply also to EA cases.…”
Section: The Influence Of Hearsay Evidencementioning
confidence: 99%
“…McCauley and Parker (2001) reported that the defendant was judged to be less credible in a child sexual abuse case than a robbery case. Finally, in two studies, the accused was judged to be less credible when evidence was presented by a child than when the same evidence was presented by a hearsay witness (Ross, Lindsay, & Marsil, 1999) or by the child via videotape (Eaton, Ball, & O'Callaghan, 2001). Should a judicial declaration of the child's competence, the age of the child, the type of case, or the mode of delivery affect the perceived credibility of the accused?…”
Section: Introductionmentioning
confidence: 99%